Molecular Identification of Selected Tick-Borne Protozoan and Bacterial Pathogens in Thoroughbred Racehorses in Cavite, Philippines - Eloiza May Galon; Adrian Miki Macalanda; Mary Margarett Garcia; Chrysler James Ibasco; Anatolio Garvida; Shengwei Ji; Iqra Zafar; Yae Hasegawa; Mingming Liu; Rochelle Haidee Ybañez; Rika Umemiya-Shirafuji; Adrian Ybañez; et al. (Pathogens, 2021)
Tick-borne diseases (TBDs) considerably impair equine health and productivity. Moreover, TBDs, particularly equine piroplasmosis, impede international movement and trade of equids, which is a vital component of the global horse racing industry. In the Philippines, horse racing is a lucrative industry generating millions of USD annually. However, information on equine TBDs is scarce. This study intended to describe molecularly the equine tick-borne infections in a racehorse park in Cavite, Philippines and identify the risk factors associated with the infections. One hundred twenty-four (n = 124) thoroughbred racehorses were sampled and screened for selected tick-borne protozoan and bacterial pathogens using polymerase chain reaction (PCR) assays. Racehorses were positive for Babesia caballi (12.10%; 15/124), Theileria equi (0.81%; 1/124), Anaplasma phagocytophilum (10.48%; 13/124), Borrelia burgdorferi sensu lato (38.71%; 48/124), A. marginale (0.81%; 1/124), and Coxiella burnetii (0.81%; 1/124). Rickettsia was not detected in the samples. Gender was determined as a significant risk factor for B. caballi infection. Sequencing analysis revealed that seven partial 18S rRNA B. caballi isolates shared 98.63–100% identity with each other and were classified as genotype A. Meanwhile, the sequence obtained from the lone T. equi-positive sample was 99.77% identical to isolates from Spain, Switzerland, China, Saudi Arabia, and South Korea, and was confirmed as genotype E based on the 18S rRNA gene. Eight Anaplasma 16S rRNA partial sequences were highly identical to A. phagocytophilum and A. ovis. Partial sequences of Borrelia 5–23S rRNA were most closely related to B. japonica and other Borrelia sp. isolates from various countries. This study reports the first molecular detection of Borrelia and Anaplasma and the identification of B. caballi and T. equi genotypes in racehorses in the Philippines. Findings from this study shall be useful in crafting equine tick and TBD control and prevention programs in the country.